Decoding the structure of GPR151 via NELiS - Yumeng Wang; Luyu Fan; Qianqian Song; Yaning Li; Jiayu Jin; Qiaoyu Zhao; Weijie Gu; Xiangyi Shi; Dianfan Li; Yao Cong; Sheng Wang (Proceedings of the National Academy of Sciences, 2026)
Structure determination of orphan G protein–coupled receptors (GPCRs) is hindered by lack of known ligands and their inherent instability during purification. Conventional thermostability screening requires ligands or purified protein, limiting its utility for orphan GPCRs. Here, we present the Nb6-Enabled Ligand-Free Stabilization Platform (NELiS)—a ligand- and purification-independent method for identifying stabilizing mutations. Applied to GPR151, an orphan GPCR enriched in habenula and implicated in neuropsychiatric disorders, NELiS identified four mutations that significantly improved thermostability and expression, allowing receptor purification. Using the stabilized and purified receptor, we further found a high-affinity, GPR151-specific nanobody that facilitated structural determination. Structural analysis revealed unconventional activation-resistant features across canonical motifs and an autoinhibitory N-terminal region occupying the orthosteric pocket. Functional studies confirmed a unique activation mechanism and the critical role of the N terminus in receptor maturation and trafficking. These results establish NELiS as a generalizable tool for structural and functional investigation of orphan GPCRs.